Cyberstalking and the adequacy of Malaysian laws: an appraisal - Mohamed, Duryana; Sardar Baig, Farheen Baig (2018)
Cyberstalking has no specific statutory definition. Sometimes the word harassment is mentioned when defining cyberstalking. This explains why cyberstalking and cyberharassment have been used interchangebly in this paper. Cyberstalking started when Internet becomes one of the most important mediums of communication in social networking. Through Internet or social media, people or cyberstalker started to follow and peep into other people activities and life styles. Later, they became obsess and trying to stalk or harass their potential victims by using various means. In most cases, cyberstalking and cyberharassment are considered as criminal offence due to their nature and bad implications to the victims. Some victims suffered depression and even committed suicide because the effect was unbearable. Their privacy have been violated and they are not able to lead a normal life. Hence, many countries such as the United States, Australia, the United Kingdom and Singapore have enacted specific law to combat cyberstalking or cyberharassment. However, the crime is still rampant particularly cyberstalking on women and children. This is based on research conducted and statements made by the relevant authorities. In Malaysia, there is no specific law and punishment on cyberstalking or cyberharassment. The laws are scattered. Previous cases on harassment were mostly involved sexual harassment and the court decisions showed that the cases were decided based on various laws such as Penal Code and the Employment Act 1955. Hence, this paper seeks to examine cyberstalking or cyberharassment and its implications to the victims, the adequacy of the existing laws in dealing with the crimes and whether there is a need to have a specific law to curb cyberstalking or cyberharassment activities. For reference, the author will refer to cyberstalking or cyberharassment laws and cases in the abovementioned countries as well as other relevant international laws.